Gap Analysis on Politeknik Negeri Bali Library Services: Expectation Versus Reality - Ni Wayan Dewinta Ayuni; Wayan Hesadijaya Utthavi; I Ketut Suparta (Soshum: Jurnal Sosial dan Humaniora, 2019)
Library in universities is the center of information and science. It can be said as the heart of university. Because of its important role, the university library must have good service. This is expected to increase the sense of comfort of library visitors in using library services. Politeknik Negeri Bali (PNB) as one of the universities in Indonesia currently has one library room located on the 2nd floor of the PNB Central Building. Based on the data, the average number of PNB library visitors in the year 2017 is only 15% of the total civitas. This number shows that PNB library has not been optimally utilized. The purpose of this research is to evaluate the PNB libray service, wheter it aready fulfill the hope of visitors. This research used 150 library visitor as sample, collected by using accidental sampling. The variables used are five service dimensions, namely tangibles, reliability, responsiveness, assurance, and emphaty. The method of analysis used in this study is gap analysis using paired t test between expected service by the visitors and PNB library service in reality. Results shows that in general, there is a significant difference between expected service by the visitors and PNB library service in reality. It also happens in five dimensions of service.